Identification and Characterization of Mirnas and Lncrnas of Coho Salmon (Oncorhynchus Kisutch) in Normal Immune Organs - Vidal-Soto, R (Academic Press, 2020)
MicroRNAs (miRNAs) and long noncoding RNAs (lncRNAs) are two relevant non-coding RNAs (ncRNAs) class. Oncorhynchus kisutch (coho salmon) is an important aquaculture pacific salmon species without report of miRNAs and a very limited register of lncRNAs. To gain knowledge about the interaction and discovery of miRNAs and lncRNAs in coho salmon we used high-throughput sequencing technology to sequence small and transcriptome libraries from three immune organs. A total of 163 mature miRNAs and 4,975 lncRNAs were discovered. The profiles of expression of both ncRNAs indicated that liver and head-kidney share relatively similar expression patterns. We identified 814 and 181 putative target sequences for 1048 lncRNAs and 47 miRNAs, respectively. The results obtained provide new information and enlarge our understanding of the diversities of ncRNAs in coho salmon. © 2019 Elsevier Inc.